2003
DOI: 10.1021/jp0301251
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Induced Dissociation of Cu Islands Supported on TiO2(110)

Abstract: Scanning tunneling microscopy studies of Cu islands grown on TiO 2 (110) demonstrate that these islands disappear from the STM images after exposure to oxygen gas (60-2000 Langmuir). Based on X-ray photoelectron spectroscopy experiments, the disappearance of the Cu islands cannot be explained by the loss of Cu from the surface or by a dramatic change in the electronic properties of the islands. The adsorption of oxygen appears to weaken the Cu-Cu bond, allowing two-dimensional (2D) islands to form on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 25 publications
7
64
0
Order By: Relevance
“…On a defective surface, however, a Ag atom sitting on a neutral Mg vacancy, V 0 s , donates two valence electrons to the four O atoms surrounding the vacancy which forms strong ionic bonds between the Ag and O atoms [74]. As we will show below, defects on oxide surfaces, such as Al 2 O 3 (0001), MgO(100), SiO 2 , and TiO 2 (110), greatly affect metal adsorption and the atomic interaction energy.…”
Section: Interface Bondingmentioning
confidence: 93%
See 2 more Smart Citations
“…On a defective surface, however, a Ag atom sitting on a neutral Mg vacancy, V 0 s , donates two valence electrons to the four O atoms surrounding the vacancy which forms strong ionic bonds between the Ag and O atoms [74]. As we will show below, defects on oxide surfaces, such as Al 2 O 3 (0001), MgO(100), SiO 2 , and TiO 2 (110), greatly affect metal adsorption and the atomic interaction energy.…”
Section: Interface Bondingmentioning
confidence: 93%
“…For example, thin epitaxial Nb films on TiO 2 (110) have (110) interface formed at room temperature. A distorted interface between Nb and TiO 2 crystal is present [90].…”
Section: Chemical Interactions At Metal/oxide Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-defined single crystal oxide is used as a model substrate to investigate the metal-oxide interaction [1]. Cu on a rutile TiO 2 (110) surface is one of the most widely investigated surfaces [2][3][4][5][6][7][8][9][10] because supported Cu on oxides has important catalytic properties [11][12][13]. These studies have demonstrated that it is usually quite difficult to obtain fine clusters less than 1 nm in size by simple vacuum evaporation of Cu on the TiO 2 (110) [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to lower surface energies of the Co oxides compared to pure Co metal the conversion of 3D Co island to 2D oxide structure is energetically favorable. The small size islands dissociate and disappear due to their conversion into 2D structures [28]. Surface morphological change from 3D island to 2D structure should enhance the XPS Co intensity.…”
Section: Interfacial Reaction Between Co Overlayer and Tio 2 Substratementioning
confidence: 99%